Communication About Food and Nutrition in the Parent Child Dyad. Issue 6 (July 2022) - Jackson, Alexandra; Sano, Yoshie; Cox, Anne E.; Lee, SuYeon; Lanigan, Jane
Purpose: Developmentally appropriate messaging interventions may be an effective way to promote healthy behaviors in young children. However, there is a gap in the literature describing communication about food and nutrition within the parent-child dyad. Thus, we explored the content, frequency, context, and purpose of parental conversations about food and nutrition. Design: Using a semi-structured interview guide, 20 in-person interviews were conducted with parents of 3 to 9 year old children living in Washington and Oregon at the location of their choice. Methods: Qualitative data was analyzed using open coding and grounded theory. Results: Three categories described communication within the dyad: purpose, content, and the bidirectional interaction between the parent and the child. Purpose included three themes: consumption, variety, and balance. Content included three themes: food-related content, body-related content, and utilizing connections. Subthemes within food-related content included properties, production, and preparation. Body-related content subthemes were utilization of food in the body and interoceptive awareness. Parents highlighted connections between the food and body-related content. Lastly, parent–child conversations about food and nutrition were dynamic and bidirectional with parents adapting to child factors. Conclusion: Our findings provide a description of parent communication about food and nutrition and suggest investigation of the purpose and content of communication and how parents tailor messages to their child.